2003
DOI: 10.1212/01.wnl.0000096173.91554.b7
|View full text |Cite
|
Sign up to set email alerts
|

Unexpectedly low prevalence and unusual characteristics of RLS in Mersin, Turkey

Abstract: The discrepancy in RLS prevalence studies (including the authors') suggests that prevalence varies among different races, thus supporting a genetic predisposition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
132
10
25

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(189 citation statements)
references
References 28 publications
(25 reference statements)
18
132
10
25
Order By: Relevance
“…Our study is the third population-based study in Germany and the fourth within German-speaking countries that used identical methods to classify cases. Compared to the other three studies [7,8,10] we observed a slightly lower overall prevalence based on the presence of the IRLSSG diagnostic criteria. However, the prevalence of 9.8 % in the Augsburg study [8] and 10.6 % in the Bruneck study [7] was assessed in considerably older populations which are known to have higher prevalences.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…Our study is the third population-based study in Germany and the fourth within German-speaking countries that used identical methods to classify cases. Compared to the other three studies [7,8,10] we observed a slightly lower overall prevalence based on the presence of the IRLSSG diagnostic criteria. However, the prevalence of 9.8 % in the Augsburg study [8] and 10.6 % in the Bruneck study [7] was assessed in considerably older populations which are known to have higher prevalences.…”
Section: Discussioncontrasting
confidence: 89%
“…Among individuals with a migrational background first, second and third generation Turkish migrants represent the largest group in the Dortmund region, but many other nationalities are also represented. Interestingly, a recent door-to-door survey in Turkey yielded a lower prevalence of 3.2 % [5,10]. The lower prevalence among migrants in our study was observed despite the process of cultural assimilation and the use of the same health care system and might indicate differences in genetic predisposition.…”
Section: Discussioncontrasting
confidence: 52%
“…However, it is known that RLS prevalence increases in parallel with age (1,2). In a study conducted in Turkey with 3234 participants, the prevalence of RLS was found to be 3.19% (14). In literature, there is a study investigating the relationship between COPD and RLS.…”
Section: Discussionmentioning
confidence: 99%
“…According to this, the patients with 1) An urge to move the legs, accompanied by a disturbing or unpleasant sensation in the legs, 2) An urge to move the legs that increases during the periods of rest or inactivity such as lying and sitting, 3) An urge to move the legs that is relieved by movements such as walking and stretching or at least decreases during the activity, or 4) An urge to move the legs, which is more severe at night than during daytime or occurs only at night were diagnosed with RLS. In the study, questionnaire items, the validity and reliability of which were proven in Turkish, were used (14). For the determination of disease severity, an assessment scale, which was standardized by IRLSSG for evaluating the severity of RLS, was utilized (15).…”
Section: Methodsmentioning
confidence: 99%
“…Türkiye'deki HBS prevalansı %2,5-7 olarak bildirilmiştir. Ülkemizde Türk Uyku Tıbbı Derneği tarafından yürütülen uyku bozuklukları epidemiyolojisinin araştırıldığı çok merkezli çalışmada; HBS sıklığı erkeklerde yüzde 3, kadınlarda yüzde 7,3 oranlarında saptanmıştır (6)(7)(8)(9)(10). HBS tanı kriterleri ilk kez 1995 tarihinde yapılandırılmış ve en son 2014 yılında Uluslararası HBS çalışma grubu tarafından yapılan düzenlemede, kesin tanı kriterleri aşağıda belirtildiği şekilde tanımlanmıştır (11): a) Bacakları hareket ettirme dürtüsüne, daima olmamakla birlikte sıklıkla bacaklardaki huzursuzluk ve rahatsızlık hisleri neden olur ya da eşlik eder, b) Bacakları hareket ettirme dürtüsüne neden olan anormal duyumun, istirahat sürecinde ya da uzanırken veya otururken kötüleşmesi, c) Bacakları hareket ettirme dürtüsüne neden olan anormal duyumun yürümek, germek gibi hareketler ile en azından aktivite süresince kısmen ya da tamamen rahatlaması, d) Bacakları hareket ettirme dürtüsüne neden olan anormal duyumun sadece istirahat ya da inaktif durumda iken olması veya akşamları ya da geceleri gündüzden daha kötü olması, e) Bahsedilen özelliklerin ortaya çıkışının birincil olarak sadece miyalji, venöz staz, bacak ödemi, artrit, bacak krampları, pozisyonel rahatsızlık ya da ayak sallama alışkanlığı gibi başka bir medikal ya da davranışsal durum nedeni ile ilişkili olmamasıdır.…”
Section: Introductionunclassified